Antibacterial activities of Musa Acuminate L. peel - Khan Chowdhury, Ahmed Jalal; John, Akbar; Fuad, Dina (2010)
N-hexane, chloroform and water extracts of (Musa acuminate L.) green and ripe banana peel were evaluated for antibacterial activity. A total of 4 bacterial strains (Salmonella typhimurium, Shigella flexneri, Bacillus subtilis, Enterrococcus faecalis) were selected and antibacterial efficiency of crude extracts were assessed by well diffusion test via measuring inhibition zones formed in agar plate at three different dosages (100mg/ml, 200mg/ml and 500mg/ml). The results showed that n-hexane and chloroform extracts of green banana peel produced significant inhibition zone against Gram-negative bacteria Salmonella typhimurium at dosage of 500mg/ml. Minimum inhibition concentration (MIC) and minimum bactericidal concentration (MBC) assay indicated that there were significant growth inhibition of the bacterial strains against water and chloroform extracts of rip banana peel and n-hexane and chloroform extraction of green banana peel (P<0.05). The GC/MS analysis of the active extracts of green banana peels from n-hexane and chloroform revealed their molecular weight and the presence of palmitic acid with 27.38% and 16.17% respectively. In conclusion present study indicated that the active extraction of n-hexane and chloroform of green banana peel has a considerable amount of potential antibacterial compounds.